1983
DOI: 10.1007/bf01955293
|View full text |Cite
|
Sign up to set email alerts
|

Metal complex formation by nicotianamine, a possible phytosiderophore

Abstract: Summary, The acid dissociation constants of nicotianamine (1) (pK l = 6.97, pK2= 9.13, pK 3 = 9.75; 0.1 M KC104, 25 ~ and the stability constants for its 1:1 complexes with bivalent metal ions (log Kcu = 18.6, log KN~ = 16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0
3

Year Published

1985
1985
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(82 citation statements)
references
References 10 publications
0
78
0
3
Order By: Relevance
“…Most of the remainder of the higher shell contributions, in particular the peak at 2.7 to 3 Å , seems to be due to Cu binding to the nonproteogenic amino acid NA, which has been shown to have a very high affinity for Cu (Beneš et al, 1983), and already earlier works suggested, on a physiological basis, that NA is involved in Cu homeostasis (Pich and Scholz, 1996;Liao et al, 2000;Irtelli et al, 2009). The explanation of the features in our EXAFS spectra with carboxylate-bound NA seems more likely than the explanation by His, as seen by the statistical analysis of the fits.…”
Section: Namentioning
confidence: 99%
“…Most of the remainder of the higher shell contributions, in particular the peak at 2.7 to 3 Å , seems to be due to Cu binding to the nonproteogenic amino acid NA, which has been shown to have a very high affinity for Cu (Beneš et al, 1983), and already earlier works suggested, on a physiological basis, that NA is involved in Cu homeostasis (Pich and Scholz, 1996;Liao et al, 2000;Irtelli et al, 2009). The explanation of the features in our EXAFS spectra with carboxylate-bound NA seems more likely than the explanation by His, as seen by the statistical analysis of the fits.…”
Section: Namentioning
confidence: 99%
“…The important role of NA in mineral homeostasis may be one of the reasons for the large number of YS family members in the rice genome. NA is well known for its capacity to chelate a variety of minerals (Benes et al, 1983), being involved in the transport of copper in the phloem and possibly performing the same function for zinc, iron and manganese (Stephan and Scholtz et al, 1993). In this regard, it is reasonable to suggest that different YS paralogs may coordinate the transport of various NA-metal complexes.…”
Section: Multiplicity Of Transporters and Members In The Gene Familiesmentioning
confidence: 99%
“…YS1 orthologs are therefore part of the primary uptake machinery specific to poaceae plants. Another class of YSL proteins, which are found in both monocots and dicots, are involved in the mobilization within the plant of metal ions, complexed either with PS or with NA, a precursor of PS with similar affinity for metals (Benes et al, 1983). Their expression is associated with vascular tissues where they are involved in the distribution of metals between organs (Koike et al, 2004;Le Jean et al, 2005;Waters et al, 2006;Zheng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%